Managing and Analyzing Employee Daily Performance Achievement Reports - Lusiana, Angraini; Misinem, . (INTI International University, 2023)
Employees at the South Sumatra Education Office, which still operates on a manual system based on Microsoft Excel, frequently become lost in piles of daily performance report sheets and data storage. In order to help employees create daily employee performance reports, this study set out to create an intuitive web-based application called the Employee Daily Performance Report Application. To make monthly employee performance reports easier to read and use, they are condensed. Use interviews and observation to compile information. The South Sumatra Education Office's monthly recapitulation of staff daily activity data is expected to be expedited by the proposed application. SUS methods were used to conduct the user acceptance of the web application, and the performance result indicates that the application may be accepted rather well.